2023
DOI: 10.1088/1361-6560/acb637
|View full text |Cite
|
Sign up to set email alerts
|

Development of optimised tissue-equivalent materials for proton therapy

Abstract: Objective: In proton therapy there is a need for proton optimised tissue-equivalent materials as existing phantom materials can produce large uncertainties in the determination of absorbed dose and range measurements. The aim of this work is to develop and characterise optimised tissue-equivalent materials for proton therapy. Approach: A mathematical model was developed to enable the formulation of epoxy-resin based tissue-equivalent materials that are optimised for all relevant interactions of protons with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, production limitations made high-density cortical bone and bone structures of more than one density infeasible. Unlike in a recent publication by Cook et al [6], the goal was not to find materials performing closer to tabulated human tissues [1] than current solutions but rather to reach the level of performance of the tissue surrogates currently used for Hounsfield unit (HU) curve calibration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, production limitations made high-density cortical bone and bone structures of more than one density infeasible. Unlike in a recent publication by Cook et al [6], the goal was not to find materials performing closer to tabulated human tissues [1] than current solutions but rather to reach the level of performance of the tissue surrogates currently used for Hounsfield unit (HU) curve calibration.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive characterization of the elemental composition of human tissues [1] and the ICRU report 44 on "Tissue Substitutes in Radiation Dosimetry" are the foundation of modern surrogates [2]. Potential candidates to expand or improve the material library are investigated to this day [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Furthermore, the accuracy of the predicted SPRs is limited to how well the tissue surrogate materials in the calibration phantom mimic real human tissue interaction properties for both diagnostic x-rays (50-150 kV) and therapeutic protons (3-300 MeV). 10 The direct translation from CT numbers to SPR is problematic as there is no univocal one-to-one relationship between CT numbers and SPRs for tissues in the human body. 11,12 It has recently been shown that stoichiometric calibration using SECT with the most commonly used set of reference tissues 13,14 can cause systematic range errors in pediatric tissues, 15 partly due to a larger fraction of oxygen in pediatric tissue compared to adults.…”
Section: Introductionmentioning
confidence: 99%
“…The calibration requires a considerable amount of effort during the commissioning of each individual scanner, as the CT numbers differ between CT scanner models, scan protocol settings (e.g., tube voltage, beam filtration and reconstruction kernel), patient size, 2–5 positioning in the CT scanner, 6 as well as image noise 7–9 . Furthermore, the accuracy of the predicted SPRs is limited to how well the tissue surrogate materials in the calibration phantom mimic real human tissue interaction properties for both diagnostic x‐rays (50–150 kV) and therapeutic protons (3–300 MeV) 10 . The direct translation from CT numbers to SPR is problematic as there is no univocal one‐to‐one relationship between CT numbers and SPRs for tissues in the human body 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Phantom materials may be used for patient‐specific quality assurance (QA), 1 machine QA and routine output checks, 2 and anthropomorphic phantoms 3 . Most of these phantom materials have been tested extensively for tissue‐ or water‐equivalence in a photon beam, but several of these validated materials are not tissue‐equivalent in a proton beam 4,5 . Less is known about the dosimetric characteristics of these materials in a therapeutic carbon ion beam.…”
Section: Introductionmentioning
confidence: 99%